La formulación de un estándar normativo de imparcialidad que incorpore la imparcialidad objetivo-cognitiva en el ordenamiento jurídico peruano: un estudio sobre la repercusión de la jurisprudencia de los tribunales internacionales de derechos humanos - Higa Silva, César (2023)
This article is a case study on the configuration of the duty of impartiality in the jurisprudential development of human rights courts and its influence on Peruvian domestic courts. In this line of reasoning, the way in which the distinction between subjective and objective impartiality —identified with the “theory of appearances”—has been constructed is analyzed and, later, the relationship between impartiality and cognitive bias is determined. This is done with the aim of criticizing the theory of appearances and proposing the formulation of a standard in which three dimensions of the guarantee of impartiality are distinguished: subjective, objective-functional and objective-cognitive. Finally, the distinction between external and internal judicial independence is addressed, and its difference with impartiality is determined.